ULTRASOUND DIAGNOSIS OF THROMBOSIS IN CANCER PATIENTS - F. S. Akhmetzianov; I. A. Kamalov (Сибирский онкологический журнал)
Purpose. To identify the relationship between ultrasonographic signs of progression of venous thrombosis and procoagulant activity of malignant tumors.Material and methods. A total of 225 cancer patients with concomitant venous thrombosis were examined. The study group (143 patients) and the control group (82 patients) were matched for tumor localization, types of venous thrombosis, prevention and treatment of venous thromboembolic complications, age and gender. The patients of the study group underwent palliative, symptomatic and diagnostic surgical procedures, and the patients of the control group underwent radical surgery for cancer. In postoperative period, all patients underwent ultrasound examination of the inferior vena cava, iliac veins and the veins of the lower extremity every 3 days for 12 days.Results. In the study group, the majority of patients had echographic signs of progression of venous thrombosis. For the control group patients, good recanalization of venous thrombosis.